Prognostic Factors for Mortality in Patients With HIV/AIDS in Sardjito Hospital - Helmi, Hamid; Subronto, Yanri Wijayanti; Wijisaksono, Doni Priambodo (Acta Interna The Journal of Internal Medicine, 2024)
Background. There are 3.8 million people infected with HIV in the Southeast Asia region. Even though it tends to fluctuate, cases of HIV AIDS infection in Indonesia continue to increase every year. HIV infection in Yogyakarta is also still relatively high. The treatment of HIV infection using ARV drugs is one of the spearheads to extend the life expectancy. The risk factors that influence the outcomes of patients receiving ARV therapy are varied. Slow immune improvement is greatly influenced by the patient's condition at the start of ARV therapy, such as age, long duration of HIV infection before therapy, specific immune activation, low CD4 count, and the period of AIDS at the start of ARV therapy.Objective. To find out the factors that significantly contributed to the mortality of patients with HIV/AIDS on ARV treatment at Sardjito Hospital.Methods. An observational study was conducted using a cohort retrospective method on HIV/AIDS patients who received ARV therapy for the first time in the period January 2008 – December 2021. Data extraction was conducted from December 2021 - February 2022. Multivariable analysis was carried out using multiple logistic regression. Survival analysis was measured by Kaplan-Meier curves.Results. The total number of HIV patients in the study was 1,591 people, with 199 patients having died. Variables associated with mortality in HIV patients in bivariate analysis were age, tuberculosis status, CD4 count, occupation, and clinical stage. Multiple logistic regression showed that occupation, CD4 count, and clinical stage were consistently associated with mortality among HIV patients. One and five-year survival rates for HIV patients were 89% and 87%.Conclusion. The CD4 count, occupation, and clinical stage of HIV are associated with mortality in HIV/AIDS patients receiving ARV treatment. Although variables other than the clinical stage are not independently related, some of these variables must still be considered in the care of HIV patients.